Pengaruh Kompetensi Pedagogik Guru terhadap Kemampuan Membaca dan Menulis Siswa SD - Afifah Intan Lestari; Nur Azmi Alwi; Inggria Kharisma (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this study is to examine the influence of teachers' pedagogical competence on elementary school students' reading and writing skills through a literature review method. The review was conducted on five scientific articles published in the last five years (2020-2024) and discussed the relationship between pedagogical competence and students' literacy skills. The results suggest that teachers with high pedagogical competence, which consists of teachers' understanding of students' characteristics, lesson planning and implementation, and evaluation, are able to improve students' literacy skills more effectively. The application of varied, contextual and student-centered learning strategies contributed to improving students' reading and writing skills. Although external factors such as the family environment are also influential, the role of the teacher remains the main factor in the literacy learning process at the primary level. The findings confirm the importance of developing teachers' pedagogical competencies through continuous training in order to improve the quality of literacy education in primary schools.